Cardiophrenic angle lymph node is an indicator of metastatic spread but not specifically peritoneal carcinomatosis in colorectal cancer patients: Results of a prospective validation study in 91 patients. Issue 6 (June 2016) - Jeune, F.; Brouquet, A.; Caramella, C.; Gayet, M.; Abdalla, S.; Verin, A.-L.; Thirot Bidault, A.; Penna, C.; Benoist, S.
Abstract: Background: The presence of cardiophrenic angle lymph node (CPALN) has been associated with the risk of peritoneal carcinomatosis (PC) in high risk colon cancer patients. Its accuracy to predict PC and its prognostic value in non-selected CRC patients has not been validated prospectively. Methods: From 2011 to 2013, all patients undergoing colectomy for colon cancer were included prospectively. Presence of CPALN was assessed on preoperative computed tomography scan by two radiologists. Surgical exploration was used as reference for the diagnosis of PC. Factors associated with presence of CPALN and progression-free survival were analyzed. Results: Ninety one patients fulfilled inclusion criteria. CPALN was detected in 36 patients (39.5%) on CT scan. At surgical exploration, PC was found in 6 patients (6.5%). Sensitivity, specificity, negative predictive value, positive predictive value and overall accuracy of CPALN on CT scan for predicting PC were 67%, 62%, 96%, 11% and 63% respectively. In multivariate analysis, the presence of distant metastases whatever the site was associated with the presence of CPALN (p = 0.03; hazard ratio HR = 3.8; confidence interval CI 95% = 1.1–13.3). In the multivariate analysis, only vascular involvement (p = 0.034, HR = 3.574, CI 95% = 1.10–11.60) was associated with progression-free survival whereas CPALN was not found to predict outcome (p = 0.893). Conclusion: CPALN is a common finding in non-selected colon cancer patients. Although in the absence of CPALN, PC can almost be excluded, its value for the diagnosis of PC is limited. Our findings support that CPALN is mainly an indicator of metastatic spread of the tumor.